2018
DOI: 10.1177/0284185118791200
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion-CT analysis for assessment of hepatocellular carcinoma lesions: diagnostic value of different perfusion maps

Abstract: Background Computed tomography liver perfusion (CTLP) has been improved in recent years, offering a variety of perfusion-parametric maps. A map that better discriminates hepatocellular carcinoma (HCC) is still to be found. Purpose To compare different CTLP maps, regarding their ability to differentiate cirrhotic or non-cirrhotic parenchyma from malignant HCC. Material and Methods Twenty-six patients (11 cirrhotic) with 50 diagnosed HCC lesions, underwent CTLP on a 128-row dual-energy CT system. Nine different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
2
6
0
1
Order By: Relevance
“…In addition, progressed HCC lesions exhibited significant changes in perfusion parameters related to hypervascularity (increased BF and BV, decreased MTT) and permeability (increased PS) as expected. These observations have been confirmed in multiple studies in patients [ 86 , 87 , 88 , 89 ]. Among available CT perfusion parameters that are based on pharmacokinetic models, Fischer et al found that a cut-off value of ≥85% HPI exhibited a sensitivity of 100%, while a cut-off value of ≥99% HPI yielded a specificity of 100% for the detection of HCCs in cirrhotic patients ( Figure 8 , [ 88 ]).…”
Section: Ct Perfusionsupporting
confidence: 66%
See 1 more Smart Citation
“…In addition, progressed HCC lesions exhibited significant changes in perfusion parameters related to hypervascularity (increased BF and BV, decreased MTT) and permeability (increased PS) as expected. These observations have been confirmed in multiple studies in patients [ 86 , 87 , 88 , 89 ]. Among available CT perfusion parameters that are based on pharmacokinetic models, Fischer et al found that a cut-off value of ≥85% HPI exhibited a sensitivity of 100%, while a cut-off value of ≥99% HPI yielded a specificity of 100% for the detection of HCCs in cirrhotic patients ( Figure 8 , [ 88 ]).…”
Section: Ct Perfusionsupporting
confidence: 66%
“…Among available CT perfusion parameters that are based on pharmacokinetic models, Fischer et al found that a cut-off value of ≥85% HPI exhibited a sensitivity of 100%, while a cut-off value of ≥99% HPI yielded a specificity of 100% for the detection of HCCs in cirrhotic patients ( Figure 8 , [ 88 ]). Recently, Hatzidakis et al highlighted that even descriptive perfusion parameters, such as the mean slope of increase, might offer high accuracy in discriminating HCC lesions from normal parenchyma ( Figure 9 , [ 89 ]). Other studies have demonstrated differences in CT perfusion parameters between HCC and hemangiomas [ 98 , 99 , 100 ], liver metastases [ 101 , 102 , 103 ], or arterioportal shunts [ 104 ], indicating that CTLP might be a useful tool for differential diagnosis between HCC and other focal liver lesions ( Table 7 ).…”
Section: Ct Perfusionmentioning
confidence: 99%
“…In the past decade, perfusion-CT (PCT) has advanced to a more sensitive imaging technique compared to multiphase-CT as it enables quantification of blood supply for both tumor and liver using a separate assessment of the arterial and portal-venous blood supply (5,6). This technique increases the sensitivity of CT scans for detecting HCC-suspicious liver lesions as it measures the arterial contribution to the tumor blood supply on the background of non-involved liver parenchyma, which generally exhibits a consistently lower level of arterialization (7). Hence, liver masses can not only be better detected, but also characterized in terms of the magnitude of blood flow (BF), blood volume (BV), vessel wall permeability (k-trans) and in particular with respect to the degree of arterial versus portal-venous vascular supply.…”
mentioning
confidence: 99%
“…The latter reflects differences in the mix (arterial±portal-venous) of blood supply between HCC, dysplastic nodules, and regenerative nodules (8). The enhanced tumor-to-liver contrast generated by arterial liver perfusion (ALP) or hepatic perfusion (HPI) color-coded maps is essential for lesion detection, also enabling the depiction of smaller (<10 mm) lesions (6,7). Previous comparative studies between biphasic or triphasic contrast-enhanced-CT and PCT have underlined the superiority of the latter (9, 10).…”
mentioning
confidence: 99%
“…Перфузионная компьютерная томография (КТ-перфузия) печени -метод лучевой диагностики, который используется для дифференциальной диагностики объемных образований и оценки результатов лечения [6][7][8]. Кроме того, этим методом можно количественно оценивать гемодинамические изменения в ткани печени, в том числе возникающие в результате прогрессирования фиброза и цирроза [9].…”
unclassified